2014
DOI: 10.1590/0103-0582201432213113
|View full text |Cite
|
Sign up to set email alerts
|

Preterm newborns at Kangaroo Mother Care: a cohort follow-up from birth to six months

Abstract: OBJECTIVE:To evaluate clinical outcomes, growth and exclusive breastfeeding rates in premature infants assisted by Kangaroo Mother Care at birth, at discharge and at six months of life. METHODS: Prospective study of a premature infants cohort assisted by Kangaroo Mother Care in a tertiary public maternity in Northeast Brazil with birth weight ≤1750g and with clinical conditions for Kangaroo care. RESULTS: The sample was composed by 137 premature infants, being 62.8% female, with average birth weight of 1365±28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
(67 reference statements)
1
8
0
10
Order By: Relevance
“…Corroborating the data found in the study [10] developed in a tertiary public maternity hospital of the Northeast Region of Brazil, which found a mean maternal age of 26±7 years in their results, and the study that found a mean age of 25.7 years [11].…”
Section: Discussionsupporting
confidence: 62%
“…Corroborating the data found in the study [10] developed in a tertiary public maternity hospital of the Northeast Region of Brazil, which found a mean maternal age of 26±7 years in their results, and the study that found a mean age of 25.7 years [11].…”
Section: Discussionsupporting
confidence: 62%
“…Este processo pode ser possível com a implantação do método canguru na UTIN observada, que contribui de forma signifi cativa para o desenvolvimento do bebê prematuro (Menezes, Garcia, Melo, & Cipolotti, 2014). O método em questão viabiliza o contato precoce entre a mãe e o bebê hospitalizado, permitindo que esta participe mais efetivamente e por mais tempo dos cuidados oferecidos ao bebê, que é estimulado através do contato direto com a pele da mãe, facilitando a amamentação e auxiliando na vinculação da díade.…”
Section: Considerações Fi Naisunclassified
“…3,7 The main benefits of KC include: institutional benefits that emphasize the reduction of the risk of crossinfection and nosocomial infection, reducing length of stay and readmissions caused by infections, define themselves as a cost-effective and cost-effectiveness model. 7,8 Regarding to maternal benefits, the method promotes the stimulation of lactation and breastfeeding, developing the mother's confidence in the role of caregiver, and generate family attachment bonds. 4 Regarding to the premature infant, by increasing breastfeeding, provides the transfer of maternal antibodies to the newborn through colostrum and contact; helps in the physical and emotional development of the newborn; stabilizes heart and respiratory rate, oxygenation and body temperature, with an increase of physiological responses.…”
Section: Introductionmentioning
confidence: 99%
“…This skin contact produces endogenous mechanisms that reduce the crying, the signs of pain and stress after painful stimulation, promotes the maintenance of homeostasis, improve neuro motor behavior as well as providing calm and serenity by listening to the mother's heart sound and the mother's voice. [7][8][9] The method is applied in three distinct stages: the first stage begins in the prenatal facing the diagnosis of highrisk pregnancy with continuity in the neonatal intensive care unit (NICU). The second stage requires clinical stability of the child, minimum weight of 1.250g, interest and mother's availability to stay with the RN the most desired and possible time in the kangaroo position.…”
Section: Introductionmentioning
confidence: 99%